Pengaruh Social Media Marketing, Lokasi, Tarif Kamar Terhadap Keputusan Menginap dengan Brand Image Sebagai Pemoderasi - Rista Angriani; Ingrid Panjaitan (Jurnal Minfo Polgan, 2026)
With Brand Image as a moderating variable, this study examines how social media marketing (SMM), location, and room rates influence the decision to stay at a star-rated hotel in Tawangmangu District, Karanganyar Regency. A purposive sampling method was used to collect data from 110 respondents through a 5-point Likert scale questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to demonstrate that all indicators met the criteria for convergent validity (outer model ≥ 0.70; AVE ≥ 0.50) and reliability (CR > 0.90). The results showed that brand image, location, and social media marketing had a positive and significant effect on the decision to stay, while room rate did not. In addition, brand image served as a moderating variable, strengthening the influence of location but weakening the influence of social media promotion and room rates on the decision to stay. The model could explain 72.6% of the variation in the decision to stay. These findings suggest that not only functional factors but also psychological factors, such as brand perception, influence stay decisions. Therefore, hotel managers are advised to strengthen their brand image and optimize digital marketing strategies and location selection to improve consumer decisions.